(untitled) (REVISTA SAYWA, 2023)
The use of PGPR (plant growth-promoting rhizobacteria), which are a group of bacteria that live in the rhizosphere of plants and produce all kinds of benefits, improving growth, availability and/or absorption of minerals (nitrates, phosphates), help in the production of hormones necessary for plant development (phytohormones). These microorganisms have various applications in organic agriculture as bio-controllers, biofertilizers and biofertilizers and protect plants against possible pathogens and improve the bioavailability of nutrients in the soil to promote plant growth. Experiences in ecological restoration of degraded ecosystems have focused on the use of arbuscular mycorrhizae and bacteria at greenhouse scale.